How to improve change-of-direction speed in junior team sport athletes-horizontal, vertical, maximal, or explosive strength training? - Keller, S.; Koob, A.; Corak, D.; von Schöning, V.; Born, D.-P. (The Journal of Strength and Conditioning Research, 2020)
The purpose of the study was to compare the effects of 4 different training methods on change-of-direction (COD) speed in junior team sport athletes. Specifically, we investigated whether horizontal load training incorporating lateral acceleration and deceleration would induce superior performance adaptations with respect to COD speed, compared with common vertically oriented maximal strength (squats and deadlifts), explosive strength (power clean and high pull), and vertical jumping exercises. Male U15 team sport athletes (n = 45) were assigned to 1 of 4 groups and performed 2 intervention training sessions per week for 4 weeks, in addition to their usual sport-specific training. Before and after the training period, COD speed, countermovement and drop jump heights, 1-legged lateral jump, and standing long jump performance were assessed. All 4 training groups improved COD speed (p = 0.01, effect size [ES] =1.35). Countermovement and 1-legged lateral jump performance improved with the horizontal load (p < 0.01, ES = 0.81 and p < 0.01, ES = 1.36), maximal (p = 0.01, ES = 0.56 and p < 0.01, ES = 1.14), and explosive strength training (p < 0.01, ES = 0.95 and p < 0.01, ES = 1.60, respectively). The standing long jump improved with the maximal (p < 0.01, ES = 1.14) and explosive strength training (p < 0.01, ES = 0.60). In conclusion, all 4 training methods improved the COD speed in junior U15 team sport athletes. These findings emphasize the importance of well-developed lower-body strength and power, which contribute to fast COD speed. From a practical perspective, conditioning programs for junior athletes can incorporate horizontally and vertically oriented exercises with similar effectiveness on COD speed.